EXAMINATION OF EMPIRICAL RELATIONSHIPS BETWEEN INDUSTRIAL ACTIVITIES AND AGRICULTURAL POLICY OUTPUTS IN NIGERIA (1970-2012) - Sunday Brownson Akpan; Samuel James Udok; Uwemedimo Eyo Okon (International Journal of Food and Agricultural Economics, 2014)
The study investigated relationships between agricultural policy output (proxy by the agricultural productivity index, agricultural GDP/total GDP and crop productivity index) and output of industrial sector (proxy by the industrial capacity utilization rate) from 1970 to 2012 period in Nigeria. The study employed time series variables obtained from the Central Bank of Nigeria (CBN), National Bureau of Statistics and Food and Agricultural Organization (FAO). Augmented Dickey-Fuller unit root test was conducted on the specified time series, and the result showed that all non-growth rate series were integrated of order one, while growth rate series were stationary at level. The two-step Engle Granger method was employed to test for the presence of cointegration among specified variables. The result revealed that variables were not co-integrated. To avoid spurious regression, the specified models for non-growth rate series were estimated at first difference of the log variables. The empirical result revealed that, the industrial activities Granger cause crop activities in Nigeria. Also, the industrial activity has insignificant relationship with agricultural productivity indices in Nigeria. The same result was also obtained for industrial activities and agricultural GDP/total GDP. However, the result further revealed that, the industrial activity has significant negative correlation with the crop productivity index in Nigeria. These imply that, agricultural production had not played significant role in industrial development in Nigeria. This result suggests that, there is no significant impact of the backward integration policy of the agricultural sector on industrial sector in Nigeria. In addition, the result revealed that, agricultural policies during liberalization era (1986 - 2012) shifted the coefficient of the industrial activities positively. Therefore, it is recommended that the agricultural production in Nigeria should be boosted so as to generate sufficient demand and raw materials for the industrial sector. Agricultural policy of the liberalization period should be promoted as an alternative way to bring on positive growth in industrial activities and hence economic development in Nigeria.